If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(4 + -5x) = -42 (4 * -3 + -5x * -3) = -42 (-12 + 15x) = -42 Solving -12 + 15x = -42 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 15x = -42 + 12 Combine like terms: -12 + 12 = 0 0 + 15x = -42 + 12 15x = -42 + 12 Combine like terms: -42 + 12 = -30 15x = -30 Divide each side by '15'. x = -2 Simplifying x = -2
| Log(x-1)=0 | | (x+8)+(x+15)=9x+40 | | y^4+2y^2-4=3 | | y^4+2y^2-4=0 | | y^4+2y^2-4=y-3 | | .125+.05+.53= | | 4x+10=3x-12 | | 149-2x=34x+17 | | -92-7=7x+20 | | 24-8x-5=6 | | 2x-3=-8 | | -45x+5y=-50 | | 6n+15=9n+27 | | 3n+5=77-69n | | 4n-9=3n-1 | | 6n+9=n+34 | | 3+5n=15*2n | | 132-2n=4n | | 3n+10=8n | | n(7)=25(2n) | | (5x-1)2=0.64 | | Y-14=31 | | Y-14=10 | | x^2-8x+9=4x-2 | | x^2-3x-5= | | 6a^2b-4ab^2=0 | | 82x-(5-3)= | | 3z-14=10 | | ln(x)+ln(y)=2 | | lnx+lny=2 | | 4x^2-16y^2=0 | | 6x^3y+2x^2y^2=0 |